Irmintrude sculdarissa: a female title in Carolingian Verona (Studi di storia medioevale e di diplomatica - Nuova Serie, 2023)
This study is divided into two parts. In the first one, the problem of the appearance and spread of the title of comitissa from the second half of the 9th century onwards is outlined, giving the main explanations that have been given to the phenomenon. The second part presents the case of Ermentrude sculdarissa, long misinterpreted as Ermentrude sculdahis. In the parchment Verona, Archivio di Stato, Corporazioni Religiose Soppresse, S. Maria in Organo App.* n. 10, the woman appears as emptrix of two lands with vineyards in the Veronese territory and as the author of a letter to Abbot Rumaldo in which she promises the donation of some of her goods to S. Maria in Organo. The aim of the study is to contextualise and attempt to explain the invention of the title sculdarissa in Carolingian Verona between the 940s and 960s.
Keywords: Carolingian Verona; Female titles; comitissa; sculdarissa